Exploring knowledge management maturity from funcionalist and interpretivist perspectives - José Enrique Arias-Pérez; Carlos Mario Durango-Yepes (Entramado)
The purpose of this article is to explore the Knowledge Management Maturity Model (KMMM) in big companies that are pioneers in the implementation of KM practices in Medellin, Colombia. The KMMM integrates the Funcionalist and Interpretivist perspectives on knowledge management and consists of four key areas: Organization and People, Processes, Technology, and Interpretation. Cluster analysis helped establishing the ranges of the five maturity levels: Initial, Awareness, Defined, Managed, and Optimized. The results showed that only two companies overcame the “Defined” level, and the best performance was achieved in the Technology key area. In conclusion, the companies have difficulties at going further the implementation of basic KM initiatives and achieving a higher level of maturity associated with the articulation of KM practices with business processes and a higher degree of appropriation and usage by individuals. This may occur because of the preponderance of the Functionalist approach in the business context and the low level of penetration and integration with the Interpretivist perspective of KM.